Low-Wage Workers and Health Insurance Coverage: Can Policymakers Target Them through Their Employers? - Stephen H. Long; M. Susan Marquis (SAGE Publishing, 2001)
Many policy initiatives to increase health insurance coverage would subsidize employers to offer coverage or subsidize employees to participate in their employers' health plans. Using data from the 1997 Robert Wood Johnson Foundation Employer Health Insurance Survey, we contrast "low-wage employers" with all other employers. Employees in low-wage businesses have significantly worse access to employment-based insurance than other employees do; they are less likely to work for an employer that offers insurance, less likely to be eligible if working in a business that offers insurance, and less likely to be enrolled if eligible. Low-wage employers contribute lower shares of premiums and offer less generous benefits than other employers do. Policies that would target subsidies to selected employers to increase insurance offers to low-wage workers are difficult to design, however, because several commonly mentioned employer characteristics (including firm size) are found to be poor indicators of low-wage worker concentration. Programs that would set minimum standards for employer plans to be eligible for "buy-ins" need to base these standards on the less generous terms offered by low-wage employers in order to effectively reach low-wage workers and their dependents.